A PROPOSED RECONCILIATION OF STANDARD AND CURRENT MATERIAL COSTS. - Benninger, L. J. (The Accounting Review, 1950)
Abstract During periods of comparatively stable prices, it is possible that the advantages of the standard pricing plan for materials, in terms of ease of costing, would outweigh the loss of a more current cost obtainable by a replacement cost method of pricing. However, if standard costs are utilized during a year of sharply rising or sharply declining prices, cost of materials used and sales will not be stated in terms of dollars of equivalent purchasing power. Cost, from a current cost standpoint, may be at variance with standard costs. It is probable that the advantage of having the replacement cost of goods at standard quantity usage both in the finished goods account and the cost of sales account would transcend the loss of keeping these accounts completely at standard cost. From the point of view of comparing cost of sales and profits, either on a product or period basis, ratios of cost to sales and profits to sales would be more readily comparable, since costs and sales will be expressed approximately in terms of dollars of the same purchasing power.